Life Events, Barriers to Care, and Outcomes Among Minority Women Experiencing Depression: A Longitudinal, Mixed-Method Examination. Issue 8 (21st August 2022) - Tieu, Lina; Walton, Quenette L.; Sherbourne, Cathy D.; Miranda, Jeanne M.; Wells, Kenneth B.; Tang, Lingqi; Williams, Pluscedia; Anderson, Gera L.; Booker-Vaughns, Juanita; Pulido, Esmeralda; Carr, Themba; Heller, S. Megan; et al.
Abstract: The long-term course of depression is not well-understood among minority women. We assessed depression trajectory, barriers to depression care, and life difficulties among minority women accessing health and social service programs as part of the Community Partners in Care study. Data include surveys ( N = 339) and interviews ( n = 58) administered at 3-year follow-up with African American and Latina women with improved versus persistent depression. The majority of the sample reported persistent depression (224/339, 66.1%), ≥1 barrier to mental health care (226/339, 72.4%), and multiple life difficulties (mean, 2.7; SD, 2.3). Many barriers to care ( i.e., related to stigma and care experience, finances, and logistics) and life difficulties ( i.e., related to finances, trauma, and relationships) were more common among individuals reporting persistent depression. Results suggest the importance of past experiences with depression treatment, ongoing barriers to care, and negative life events as contributors to inequities in depression outcomes experienced by minority women.